Proceedings of the 2017 Conference on Empirical Methods in Natural Language Processing 2017
DOI: 10.18653/v1/d17-1229
|View full text |Cite
|
Sign up to set email alerts
|

Preserving Distributional Information in Dialogue Act Classification

Abstract: This paper introduces a novel training/decoding strategy for sequence labeling. Instead of greedily choosing a label at each time step, and using it for the next prediction, we retain the probability distribution over the current label, and pass this distribution to the next prediction. This approach allows us to avoid the effect of label bias and error propagation in sequence learning/decoding. Our experiments on dialogue act classification demonstrate the effectiveness of this approach. Even though our under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…• UCI [44] method embeds contextual information of utterance via hierarchical CNN/RNN for DA classification. • PDI [45] method predicts the next label based on the current label probability distribution to avoid label bias. • DRLM-Conditional [46] method is a latent variable recurrent neural network architecture for jointly modeling utterances and DA labels.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…• UCI [44] method embeds contextual information of utterance via hierarchical CNN/RNN for DA classification. • PDI [45] method predicts the next label based on the current label probability distribution to avoid label bias. • DRLM-Conditional [46] method is a latent variable recurrent neural network architecture for jointly modeling utterances and DA labels.…”
Section: Results and Analysismentioning
confidence: 99%
“…• DMN [23] methods is a DMN based method for sentiment classification, where BiLSTM is used for sentences embedding. • ADC [47] and PDI [45] methds are acoustic and discourse classification based on HMM and SVM. • GAN [48] method is a generative neural network which incorporates attention technique and a label-to-label connection.…”
Section: Results and Analysismentioning
confidence: 99%
“…Tran et al, 2017b;Chen et al, 2018;Li et al, 2019;Raheja & Tetreault, 2019). Tran et al (2017c) also observed that propagating uncertainty information concerning the previous predictions can lead to the prediction of better dialog act sequences. Finally, most of the studies that approach the task as a sequence labeling problem also rely on Conditional Random Fields (CRFs) (e.g.…”
Section: Automatic Dialog Act Recognitionmentioning
confidence: 93%
“…Usando esta abordagem eles alcançaram uma taxa de acerto de 74,5% no corpus SwDA e 63,3% no corpus HCRC Map Task Corpus (MapTask). Mais tarde, o desempenho no corpus SwDA foi melhorado para 75,6% usando um método baseado na propagação de informação de incerteza sobre as previsões anteriores (Tran et al, 2017c). Para além disso, utilizando mecanismos de atenção aplicadosàs células das camadas recorrentes no contexto de um modelo generativo, alcançaram uma taxa de acerto de 74,2% no corpus SwDA e 65,94% no corpus MapTask (Tran et al, 2017a).…”
Section: Estado Da Arte Em Reconhecimento De Actos De Diálogounclassified